HUBUNGAN PENGETAHUAN SISWA SISWI TENTANG KEBERSIHAN GIGI DAN MULUT DENGAN KEJADIAN KARIES GIGI DI SDN 076714 HILIWAITO - GANDA SIGALINGGING; NURHIDAYANTI WARUHU (LP2MTBM MAKARIOZ, 2019)
Dental caries in children ranks first as a chronic disease in school-age children. The prevalence of dental caries in children in Indonesia reaches 53.2%. Children become vulnerable to nutritional deficiencies, so that body weight can shrink dramatically. In addition, tooth decay can also affect overall child health. If tooth decay is not treated properly and properly it can cause infections to spread to the brain. The aim is to analyze the relationship between students' knowledge about oral health and dental caries in SD N 076714 Hiliwaito, West Mendrehe District, West Nias Regency. The population in this study were all students in grades 4 through 6 totaling 63 people, the entire population was sampled for 63 people (total sampling) using the chi-square test. The results showed that the relationship of students' knowledge about dental and oral health with the incidence of dental caries with a p value = 0,000. To parents to introduce a toothbrush early and clean teeth and mouth children 2 times a day, especially at night before going to bed. The school should give instructions to students about dental and mouth care and its relationship with health through school UKS activities.